Factor on Instructional Leadership of the School Administrators Affecting The Effectiveness of Academic Affairs Management in School under the Nakhon Phanom Primary Educational Service Area Office 1 - Kullawong, Kritsada; Hanrin, Chanwit; Puangyod, Paitoon (Rajapark Journal, 2023)
The purposes of this research were (1) to investigate the instructional leadership of school administrators, (2) to investigate the effectively academic affairs management in school, (3) analysis of the relationship between the instructional leadership of school administrators to effectively academic affairs management in school, and (4) find the instructional leadership of school administrators are good predictors of effective academic affairs management in school under the Nakhon Phanom Primary Educational Service Area Office 1. The samples was comprised of 346 administrators and teachers. The tool used for data collection was a 5 point rating scale questionnaire. The results were found that (1) Factor on instructional leadership of the school administrator have been operated at a high level. (2) The effectiveness of academic affairs management in school was at a high level. (3) The factors on instructional leadership of the school administrator and the effectiveness of academic affairs management in school have positive relation at a .01 level of significance and .72 level of correlation coefficient. (4) The factors on instructional leadership of the school administrator have predictive power in the effectiveness of academic affairs management in school under the Nakhon Phanom Primary Educational Service Area Office 1 and shared values with showed the predictive power at 54 percent and revealed 5 predictive variables were school conditions that are conducive to learning (X3), teacher professional development (X4), curriculum and instruction administration (X2), education quality assessment (X7) and effective leader (X6). The regressive equation in raw scores and standardized score were as follows; The predictive equation of raw scores was: Y’ = 2.19 + .12 X3 + .11 X4+ .09 X2 + .08 X7 + .06 X6